Desarrollo de germoplasma - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
During 1981 the introduction of germplasm was continued with an additional 147 clones from Brazil in the form of aseptic meristem cultures. Cassava germplasm bank evaluation for adaptation, resistance to diseases and pests, yield, and root quality is in progress in the north coast of Colombia (Media Luna, Fonseca, and Valledupar), Carimagua (Llanos Orientales), Popayan, and Palmira. General characteristics of germplasm accessions include: low yield potential of the majority of existing accessions (low HI); low frequency of accessions with high resistance to any given disease or pest; very low frequency of accessions having combined high resistance to all diseases and pests in a given region; limited range of adaptation of a given accession: much variability to be exploited in breeding exists. Gene pools are being formed for each edaphoclimatic zone. Studies on methods for improving selection efficiency by early generation selection within cassava-growing edaphoclimatic zones in Colombia are being continued. Advances in screening for early maturity, the use of herbicide mixtures for seeds and transplants, and the reevaluation of accessions selectedfor low root HCN levels are reported. (CIAT)